Malay ornament design in modern Malaysian painting volume 2 / Haslinda Abd Razak - Abd Razak, Haslinda (2017)
Outlines tracing of Ismail Mat Hussin painting entitled The Mak Yong Performance, shown three categories of performers that completed the group, which was; 1 - The main female figure was differentiated with headgear and exaggerated design on its clothing became the focal points in the composition, 2 - Four male figures that was represented as musicians with different traditional musical instruments, 3 - Six female figural dancers that featured in berkemban that accompanied the Mak Yong characters.